Utilizating Artificial Intelligence Magic School Apps and Invideo. Ai In Designing Lesson Plans - Ratu Sarah Pujasari; Melisa Sri; Yuyus Saputra; Nanak Hikmatullah; Santiana Santiana (Script Journal: Journal of Linguistics and English Teaching, 2026)
Background: The digital era requires the realm of education to continue to develop in integrating innovative approaches, especially when designing lesson plansor learning plans. This study explored the potential of artificial intelligence, Artificial Intelligence (AI), with a focus on two main platforms, namely magic school apps and invideo.ai. The researchers investigated how the Magic School Apps and Invideo applications simplify learningdesign by producing innovative learning plans that can be adapted to learning objectives, class activities, and required assessments according to therequested promt. Methodology This study used a qualitative descriptive case study to investigate the phenomenon of using artificial intelligence at the tertiary level in TechnologyEnhanced Language Learning courses. Six Participants in this research are students        in the TELL course. In collecting data the researchers interviewed these students and collect learning process information related to the use of Magic school Ai and invideo.Ai. In analyzing the data the researchers used thematic analysis. Findings: The researchers analyzed the data and they found five themes. The themes are (1) Initial Impressions and Ease of Use, (2) Feature Utility and Variety,(3) Learning Curve and Familiarity, (4) Potential in Teaching and Learning, (5) Concerns About AI Limitations. Conclusion: Exploring the development and future direction of AI in learning plans also has limitations, such as dependence on created content, this requires lecturer supervision to ensure quality and looks to the future where AI can be integrated as an adaptive learning platform and real time assessment tool to further personalize the learning experience. Originality: The issue of the utilization of Artificial Intelligence magic School AI and Invideo.AI on classroom context.